Integrated assessment of the hydraulic and structural performance of the OBREC device in the Gulf of Naples, Italy. (August 2020) - Palma, Giuseppina; Contestabile, Pasquale; Zanuttigh, Barbara; Formentin, Sara Mizar; Vicinanza, Diego
Abstract: The aim of this work is to analyze the performance of the Overtopping Breakwater for Energy Conversion (OBREC), developed by the team of the University of Campania and installed at prototype scale in the port of Naples. It is a multifunctional coastal structure aimed to protect harbors and produce energy, based on the overtopping principle. This device has been preliminary analyzed by means of experimental and numerical investigations. This contribution provides for the first time an integrated assessment of the OBREC hydraulic and structural performance, by means of the measurements collected at the prototype installation and of numerical modelling i.e. methodologies not affected by the scale effects. The numerical model, developed in the openFOAM environment, is calibrated on the field data gathered during a storm event and is then applied to extend the information related to the OBREC response under the typical wave climate. The results obtained are proposed in terms of overtopping discharge rates and pressures acting along the OBREC profile, under several sea states. Based on these results some recommendations and indications regarding the optimal cross section design are given to maximize the energy production, without compromising the structural stability, and to promote the device exploitability.